WHAT LECTURERS SAY: PERSPECTIVES ON MASTER STUDENTS' SPEAKING PROFICIENCY AT ONE PUBLIC UNIVERSITY IN JAMBI - Samsinar; Muhklas Abrar; Ali (Language and Education Journal, 2025)
This study examines the lecturers' perceptions of the speaking skills of master's students in the English Education program at a public university in Jambi. It discusses how lecturers evaluate their students' speaking abilities, identifies the main strengths and weaknesses, and addresses the pedagogical and institutional implications within the context of academic discourse. Three lecturers participated in semi-structured interviews to supply data for a qualitative case study. The results reveal striking differences in student proficiency; some students struggled with fluency, a limited vocabulary, and a lack of confidence when speaking English, while others demonstrated confidence, communicative competence, and the ability to convey meaning successfully. The findings also reveal that lecturers tend to prioritize fluency and coherence over grammatical accuracy, employing adaptive teaching strategies such as code-switching, scaffolding, and encouraging feedback to meet the diverse needs of their student body. These results highlight the disparity between institutional expectations and actual student performance, as well as the need for stronger language support systems. Each of these insights underscores the importance of aligning student needs with instructional support in the EMI environment. Overall, the observations highlight the importance of aligning student needs with instructional support in the EMI context.